Transperitonealna laparoskopska radikalna nefrektomija - Zupančič, Marko (Zdravniški vestnik, 2006)
Background Our purpose was to present our experiences with transperitoneal laparoscopic radical nephrectomy in patients with renal cancer and to compare our results with those published in the literature. Patients and methods Between June 2000 and March 2006 in 11 patients with age range 39 to 82 years (mean 56.3 years) in whom the renal cancer was found, we tried to do transperitoneal laparoscopic radical nephrectomy. For diagnosis of renal cancer abdominal ultrasound, CT scan, chest X-ray, blood and urine tests were done. During operative procedures we measured the operating time and blood loss. After procedure we registered analgesics needs of patients, hospital stay and patient's return to normal activity. In all cases pathological examination of the specimen was done. Results Laparoscopic procedure was performed entirely in 8 patients. We have to reoperate 1 patient on second dayafter the first procedure because of the bleeding caused by blood coagulation disturbances. In 3 patients conversion into classical technique was necessary (major bleeding or technical difficulties). In 2 patients among 8 cases we finished the laparoscopic procedure using the hand-assisted technique. All patients had a renal cell carcinoma, 4 patients (50%) in stage pT1, 2 (25 %) in stage pT2 and 2 (25%) in stage pT3. The mean operating time was 209 minutes. Two patients were transfused with packed red cells. Analgesics were in all patients necessary on the day of operating procedure and the day after. The postoperative hospitalization range was 4 to 7 days. The patients began with normal physical activity 5 to 5 day after surgery. Conclusions Our initial results with transperitoneal laparoscopic radical nephrectomy are comparable with those published in the literature. We believe that use of proper vascular staplers, other needful instruments and more experiences can significantly reduce the operating time.
Keywords: Diagnosis; Kidney Neoplasms; laparoskopska kirurgija; Ledvica, novotvorbe; ledvice; Nefrektomija; Nephrectomy; rak (medicina); Surgery; Surgery, Laparoscopic; Treatment Outcome; Zdravljenje, izid